The Current Landscape of US Pediatric Anesthesiologists: Demographic Characteristics and Geographic Distribution. Issue 6 (December 2016) - Muffly, Matthew K.; Muffly, Tyler M.; Weterings, Robbie; Singleton, Mark; Honkanen, Anita
Abstract : (Abstracted from Anesth Analg, 123(1):179–185, 2016) This article details a concerted attempt to collect data on pediatric anesthesiologist in the United States. Individuals identified as pediatric anesthesiologists practicing in the United States, as reported by 4 main sources: the American Board of Anesthesiology, the National Provider Identifier registry, the Healthgrades.com database, and the Society for Pediatric Anesthesia membership list, were merged in an attempt to create a comprehensive database.